2005
DOI: 10.1159/000088037
|View full text |Cite
|
Sign up to set email alerts
|

Aminiotic Fluid and Intrauterine Growth Restriction in a Gastroschisis Fetal Rat Model

Abstract: Fetuses with digestive anomalies such as gastroschisis may present intrauterine growth restriction (IUGR) and shortened intestines. Objective: The aim of this study was to assess the influence caused by amniotic fluid (AF) in intestinal length and somatic growth in an experimental gastroschisis fetal model at two distinct gestational ages. Material and Method: Fetal rats were operated according to Correia-Pinto on 2 different days of gestation: day 18.5 (group I) and day 19.5 (group II). Each group was divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…0.001). BW was not as altered in the subgroups (p = 0.793) as in the E18.5 and E19.5 groups (p = 0.271); these results are different from those of Albert et al [2] and FranchiTeixeira et al [27] who found a smaller BW in gastroschisis fetuses.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…0.001). BW was not as altered in the subgroups (p = 0.793) as in the E18.5 and E19.5 groups (p = 0.271); these results are different from those of Albert et al [2] and FranchiTeixeira et al [27] who found a smaller BW in gastroschisis fetuses.…”
Section: Discussioncontrasting
confidence: 70%
“…0.001), but not between E18.5 and E19.5; mucosal thickening was also verified in lamb gastroschisis, with corresponding enlargement of the submucosa [4] . The same occurred in rabbit gastroschisis [27] and it seems that this thickening of the intestinal wall is related with a decrease in disaccharidase activity, contributing to neonatal intestinal malabsorption [17] .…”
Section: Discussionmentioning
confidence: 76%
“…These studies support the hypothesis that in utero protein and fluid loss from the bowel to the amniotic fluid may account for the raised incidence of growth restriction, oligohydramnios, and intrauterine death that occur in these at-risk pregnancies. A rat model has shown that gastroschisis had a direct correlation with IUGR, but that the time of exposure to the amniotic fluid had no influence on body weight, but did interfere with intestinal length [33] .…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy include concerns about fetal growth and liquor volume as well as progression of bowel dilatation evident on ultrasound which prompted earlier delivery. There is certainly both human and animal evidence that fetal growth restriction occurs in gastroschisis [10,11] .…”
Section: Discussionmentioning
confidence: 99%